Prevalence and characteristics of extended-spectrum β-lactamase genes in Escherichia coli isolated from piglets with post-weaning diarrhea in Heilongjiang province, China - Xu, Guofeng; An, Wei; Wang, Hongdong; Zhang, Xiuying (Frontiers in Microbiology, 2015)
The purpose of this study was to investigate the prevalence of extended spectrum β-lactamase (ESBL) genes in Escherichia coli isolated from post-weaning diarrhea (PWD) piglets in Heilongjiang province, China. Of 458 E. coli isolated from 589 fecal samples from PWD piglets, a total of 198 isolates were confirmed as ESBL producers by the double-disk synergy test (DDST). Polymerase chain reaction (PCR) and sequencing were performed to identify genes for ESBL, PMQR, and integrons. Of the 198 isolates, blaCTX-M and blaTEM were detected in 191 and 149 isolates, respectively. Sequencing revealed that ten blaCTX-M subtypes were detected, and blaCTX-M-14 was the most prevalent, followed by blaCTX-M-55 and blaCTX-M-65. Of the 149 TEM-positive strains, four were blaTEM-52 and the rest were blaTEM-1. Among the 198 ESBL-positive isolates, 173 isolates were found to harbor at least one PMQR genes, with oqxAB, qnrS, qnrB, qepA, and aac(6′)-Ib-cr being detected alone or in combination in 125, 114, 26, 24, and 45 strains, respectively. 155 ESBL-positive isolates were also positive for class I integron (int1), and eight different gene cassette arrays were confirmed in 110 isolates by restriction fragment length polymorphism (RFLP) and DNA sequencing analyses, with predominance of dfrA17-aadA5, dfrA12-orfF-aadA2, and dfrA1-aadA1 arrays. To the best of our knowledge, this is the first report of the blaTEM-52 gene in pig E. coli isolates in China and this is also the first description of the coexistence of the qnrB, qnrS, aac(6′)-Ib-cr, qepA, and oqxAB genes in one E. coli strain.